2016
DOI: 10.5851/kosfa.2016.36.1.122
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mixed Probiotic Starter Cultures Isolated from Kimchi on Physicochemical and Functional Properties, and Volatile Compounds of Fermented Hams

Abstract: The objective of this study was to investigate the effects of mixed starter cultures isolated from kimchi on physicochemical properties, functionality and flavors of fermented ham. Physicochemical properties, microbial counts, shear force, cholesterol contents and volatile compounds of fermented ham were investigated during processing (curing and ripening time). Curing process for 7 d increased saltiness, however, decreased hunter color values (L, a, and b values). Ripening process for 21 d increased most para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Most alcohols are derived from the metabolism of carbohydrates by microorganisms but are also considered as markers of secondary oxidation of fatty acids. Other authors found ethanol as the most abundant alcohol in Macedonian fermented sausages (Sulejmani, & Demiri, 2019), Thai fermented sausages (Rotsatchakul, Visesanguan, Smitinont, & Chaiseri, 2009), and fermented hams (Kim et al, 2016). The presence of ester compounds, as also highlighted by the Rzepkowska, Zielińska, Ołdak, & Kołożyn Krajewska (2017), can contribute to the fruity aroma notes associated with a high acceptance of traditional dry sausages.…”
Section: Discussionmentioning
confidence: 93%
“…Most alcohols are derived from the metabolism of carbohydrates by microorganisms but are also considered as markers of secondary oxidation of fatty acids. Other authors found ethanol as the most abundant alcohol in Macedonian fermented sausages (Sulejmani, & Demiri, 2019), Thai fermented sausages (Rotsatchakul, Visesanguan, Smitinont, & Chaiseri, 2009), and fermented hams (Kim et al, 2016). The presence of ester compounds, as also highlighted by the Rzepkowska, Zielińska, Ołdak, & Kołożyn Krajewska (2017), can contribute to the fruity aroma notes associated with a high acceptance of traditional dry sausages.…”
Section: Discussionmentioning
confidence: 93%
“…These results agree with those reported by Sa ´nchez (2005), who considered the influence on the pH of the LAB growth, that fermented the surface sugars during the first drying steps. In fact, Sa ´nchez (2005) and Kim et al (2016) reported the highest pH values for lots not inoculated with LAB. In our work, significant differences (p \ 0.05) were found between the pH of lot 3 (with only LAB added), lot 1 and 2.…”
Section: Physicochemical Parametersmentioning
confidence: 93%
“…The color of the sausages inoculated with LAB strains changed over time. Young et al (2016) reported that the color of fermented meat products changed during the curing process. It was concluded that this phenomenon led to an increased preference for the appearance of the fermented sausages in the present study.…”
Section: Ta B L E 1 Texture Characterizationsmentioning
confidence: 99%